KAPASITAS LENTUR KOLOM BETON BERTULANGAN BAMBU PETUNG POLOS - Tika Retno Handayani; Agus Setiya Budi; Bambang Santosa (Matriks Teknik Sipil, 2014)
Steel Reinforcement is the product of mine whose existence will someday be depleted. To overcome these problems, as an alternative effort usingbamboo reinforcement that cheap and has high strength. Bamboo is a plant included Bamboidae, one member of the sub-family of grasses and it isgrowing very fast. This study uses an experimental method with a total of 7 samples objects. The sample used in this research is a concrete blockmeasuring 150 x 150 x 1500 mm. The two columns using plain steel reinforcement, two columns not using any reinforcement and three othersusing plain Petung bamboo. Bending test performed at 28 days with third-point loading method. Value ofthe flexuralcapacity ofthe column usingplain Petung when it's yield condition is 110,33ton mm. The maximumflexural capacity dan the failure flexural capacity ofthe columnusing plainPetung bamboo is 359,68ton mm. The maximumaxial forceandaxial forceobtained from column without reinforcement was1,15to collapseton.Column using plain Petung bamboohasa maximumaxial forceandaxial forcecollapsereachedthe1,6tons. Percentageincrease incolumnaxialforcecolumn using plain Petung bambooofunreinforcedcolumnis39,13%.Crack pattern on a block of concrete with steel reinforcement in concretebeams and bamboo with plain Petung bars are located between 1 / 3 spans the middle. Such a collapse is included in the bending collapse.